Transformation Of Sustainable Islamic Fashion Business Integrating Circular And Islamic Economic Principles - Nor Aina; Wahyu Akbar; Naufatti Aufa; Ma Tin Cho Mar (Journal of Islamic Economics Perspectives, 2025)
This study aims to examine in depth how the integration between the concepts of circular economy and Islamic economics can form a sustainable fashion business model, as well as make a real contribution to environmental preservation, social justice, and spiritual well-being. The background of this study is the environmental impact of the fast fashion industry and the need for responsible production-consumption patterns. Using a qualitative approach through a literature study of more than 60 references, the findings show the alignment between the 5R principles (Reduce, Reuse, Recycle, Repair, Recovery) in the circular economy with Islamic values such as justice, balance, and social welfare, which are in line with maqashid al-syariah. The research also highlights the role of technology in accelerating the transformation of the sustainable fashion industry as well as Indonesia's great potential to integrate Islamic values with circular practices, supported by a large Muslim population, growing awareness of sustainability, and policy support. However, challenges such as the lack of recycling infrastructure, low consumer literacy, and the absence of sharia standards for sustainability remain obstacles. This study contributes a holistic conceptual perspective by incorporating ecological and spiritual dimensions in the development of sustainable Islamic fashion businesses.